Classroom Experiences of Creative Thinking - Wijirahayu, Suciana; Ayundhari, Vidia Lantari (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study examines the application of higher order thinking in a real classroom practices. Some theories are presented to give a solid ground for examining the evidence. The experience of joining the instruction and assessment will also be elaborated. The course description, classroom activities and assessment are presented to give evidence on how HOTS was applied by the lecturers and the students. The scope of discussion in this study is limited on creative thinking through teaching strategies and assessment in Research Method and MA Thesis Writing subjects at Sofia University “St. Kliment Ohridski”, Bulgaria. Critical linguistic and cultural approach used in both of the courses coloured the result of the creative thinking exposed in this qualitative  research. Information on how teaching-learning and assessment could be done more creatively especially by Indonesian teachers to facilitate appropriate teaching strategies and learning environments to support the English as a foreign language learning competence  growth and their flexible attitudes are one of the objectives.